Bacterial Organisms Causing Urinary Tract Infection and their Correlation with Vitamin-D Deficiency in Pediatric Patients Presenting at Tertiary Care Hospital in Pakistan - Faryal Yunus, Nusrat Ali, Humera Javed, Sara Najeeb, Sabahat Rehman, Maliha Ansari, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary tract infection is very common among the pediatrics. The systematic effects of vitamin D on the pathogens showed its vital role in immune regulation of the body. Objective: The study aimed to assess the status of vitamin-D in the children suffering from urinary tract infection. Study design: It is a cross-sectional study with statistical approach, conducted at HBS Medical and Dental College / HBS General Hospital Islamabad Material and Methods: The study was conducted on 91 patients visited the pediatric department of the hospital. The study was conducted for six month duration From November 2021 to April 2022. Out of the 91 patients included, the 53 were kept in the experimental group and 38 were kept in the control group. The average age of the patients who participated in this study was 3.86 ± 2.93 years in the case of experimental group while the other hand average age of the patients in the control group was 3.15 ± 3.02. Results: For this study, 91 patients were selected. Among these 91 patients, 53 were kept in the experimental group and 38 were kept in the control group. The average age of the patients who participated in this study was 3.86 ± 2.93 years in the case of experimental group while the other hand average age of the patients in the control group was 3.15 ± 3.02. The patients suffering from some UTI infections have a relatively lower level of vitamin D. For UTI infections, E. coli is the most common agent. However, other microbes are also thought to be the causative agent for this infection like P. aeruginosa, K. pneumonia, S. aureus, etc. Conclusion: Vitamin D is present in less amount in patients suffering from some urinary tract infections. Therefore a relationship exists between the level of vitamin D and urinary tract infections. Therefore by this study, we can predict that vitamin D therapy can be used to treat UTIs and prevent their repetition. For UTI infections, E. coli is the most common agent.However, there is a need for a large scale study for the more elaborated validations of this study. Keywords: Vitamin D, urinary tract infection and pediatrics.